PHILIPS P 08. 672 L, AFRIQUE. One 12-inch mono disc of the series "Voyages Autour du Monde". FF 19, 95. (International Library of African Music, 1969)
If it is conceded that modern forms of African Music deserve the interest of the musicologist we must accept the arrangements by de Paur of the songs from Ghana, Nigeria, and Kenya which almost fill the first side of the disc. The music is in no other way different from that which has been made known throughout the world by Keita Fodeba's "Ballets Africaines”. In fact, on side two we find mainly music from the Senegal which seems to be performed by Fordeba's ensemble.
Keywords: African Music